Elements of vulnerability in adults with disabilities after neurological injury: integrative review (Research, Society and Development, 2022)
Objective: to identify the vulnerability situations of adults with motor disabilities after neurological injury. Method: an integrative review, with a search in August 2020 based on MEDLINE, LILACS, BDENF, SciELO and PubMed. The synthesis and interpretation of the results focused on the theory of Meleis Transitions and Ayres' concept of vulnerability. Results: 77 articles were selected, with a predominance of articles published in 2014, carried out in Brazil, with a sample of people with spinal cord injury, with level of evidence VI, derived from the PubMed portal and published in the English language. There was a predominance of situations in the Personal / Individual dimension, with greater frequency regarding the physical situation. Conclusion: We identified situations that facilitate and inhibit vulnerability in the Personal / Individual, Society / Social and Community / Programmatic dimensions.